Exploring the influence of political connections and managerial overconfidence on R&D intensity in China's large-scale private sector firms. (January 2018) - Wang, Delu; Sutherland, Dylan; Ning, Lutao; Wang, Yuandi; Pan, Xin
Abstract: Political ties and managerial cognitive biases, specifically overconfidence, have been identified as affecting firm-level R&D processes and outcomes. Here we further conceptually and empirically explore how these two factors may influence R&D intensity in an emerging market context. Our empirical results, based on panel data from 1293 Chinese publicly listed firms (between 2010 and 2014) show, contrary to some previous research, that stronger formal political ties somewhat reduce firm-level R&D intensity. Greater overconfidence in managers, by contrast, increases R&D intensity. Interestingly, moreover, overconfidence positively moderates the relationship between political ties and R&D intensity to the extent that the weak negative relationship becomes positive in the presence of overconfidence. Our results highlight the role of managerial mindset as an important determinant of R&D intensity in the emerging market context. Highlights: We explore drivers of innovation intensity in an emerging market context, China. Political ties by themselves lead to lower innovation intensity. Managerial cognitive bias, however, is a driver of innovation intensity in China. It moderates, moreover, the relationship between political ties and R&D intensity. This is likely because it leads to qualitatively different, explorative innovation.